Can Natural Products be Used to Overcome the Limitations of Colorectal Cancer Immunotherapy? - Dong, Jiahuan; Qian, Yufan; Zhang, Guangtao; Lu, Lu; Zhang, Shengan; Ji, Guang; Zhao, Aiguang; Xu, Hanchen (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is a common cancer of the digestive system that endangers human health. Immunotherapy is widely used in the treatment of patients with cancer. Some patients with dMMR/MSI-H CRC benefit from treatments that use immune checkpoint inhibitors, but most CRC patients are not sensitive to immunotherapy. Furthermore, internal resistance and immune escape lead to a reduced immunotherapy response. Therefore, the development of an effective combination therapy to improve the response rate to immunotherapy is a goal of cancer research. Natural products are potential candidates for comprehensive cancer treatments due to their wide range of immunomodulatory effects through multifactorial underlying mechanisms. In this review, we summarize the challenges in the treatment of CRC and assess the immunomodulatory effects of natural products and their active components. Our work suggests that natural products represent potential options for combined CRC immunotherapy.